PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI ITE: The Crimination of Persons of Criminal Actions Through Information and Electronic Transactions Law - Waskita, Wira Yudha Rangga; Sutrisno (AMICUS CURIAE, 2024)
A crime without the right to distribute electronic documents containing insults and/or defamation (Decision number 111/Pid.Sus/2022/Pn Mtr). The main issues are 1) How are the actions of the perpetrators of criminal acts without the right to distribute Electronic Information which contains insults and/or defamation content is appropriate or not subject to Article 27 paragraph (3) jo. Article 45 paragraph (3) of Information and Transaction Law (Study of decision No.111/Pid.Sus/2022/PN Mtr) ? 2) How are the criminal sanctions against the perpetrators of the criminal act of Defamation in accordance with the purpose of punishment? (Put No.111/Pid.Sus/2022/PN Mtr). This study uses a descriptive type of normative legal research using secondary data which is analyzed qualitatively using deductive inferences. The conclusions of the study are 1) The sentence of the judge in the decision number 111/Pid.Sus/2022/Pn Mtr ​​is incorrect based on Article 27 paragraph (3) jo. Article 45 paragraph (3) of Information and Transaction Law 2) Criminal sanctions against perpetrators of criminal acts without distribution rights Electronic Information that contain insults and/or content accessible. or defamation in decision number 111/Pid.Sus/2022/Pn Mtr ​​is not in accordance with the purpose of sentencing.